Poirot. Series 6 [videorecording (DVD)] - Christie, Agatha, 1890-1976 (Masterpiece theatre (Television program), 2012)
Agatha Christie's famous detective investigates a murder on a wealthy man's estate during the holiday season, a series of thefts at a hostel, a case of abduction and murder in France, and a murder that can only be solved by communicating with a single, silent witness.